ChemInform Abstract: Modification of Nucleic Acids by Azobenzene Derivatives and Their Applications in Biotechnology and Nanotechnology. Issue 35 (September 2015) - Li, Jing; Wang, Xingyu; Liang, Xingguo
Abstract Review: [69 refs.